Returns to social capital among traders - Fafchamps, Marcel; Minten, Bart (International Food Policy Research Institute, 1998)
Using data on agricultural traders in Madagascar, this paper shows that social capital has a large effect on efficiency. Better connected traders are shown to have significantly larger sales and gross margins than less connected traders after controlling for physical and human inputs. The analysis indicates that three dimensions of social network capital should be distinguished: relationships with other traders, which help firms economize on transactions costs; relationships with individuals who can help in times of financial difficulties, which insure traders against liquidity risk; and family relationships, which reduce efficiency, possibly because of measurement error. Social network capital enables traders to deal with each other in a more trustworthy manner by granting and receiving credit, exchanging price information, and economizing on quality inspection. Schooling is correlated with the use of superior modes of transaction but needs to be complemented by social network capital.